The Division of Mapuche Lands in Reduction Gallardo Tranamil, 1979-1985 [la División de Las Tierras Mapuche en la Reducción Gallardo Tranamil, 1979-1985] - Canales-Tapia, P (Universidad de Tarapaca, 2020)
This paper analyzes and describes the context and application of Decree Law 2,568, which liquidated the Mapuche lands, beginning in 1979, within a Mapuche reduction in the province of Cautin, in the Araucania region. The investigation presents antecedents of the common life of said reduction and its inhabitants; the political picture that surrounded this process and the stories of the Mapuche affected by the rapid and arbitrary application of this legal body in times of dictatorship. © 2020 Universidad de Tarapaca - Facultad de Educacion y Humanidades.